The effect of ketamine on emergence agitation in children: A systematic review and meta‐analysis - Ng, Ka Ting; Sarode, Deep; Lai, Yuen Sin; Teoh, Wan Yi; Wang, Chew Yin (Wiley, 2019)
Background: Ketamine is believed to reduce the incidence of emergence agitation in children undergoing surgery or procedure. However, recent randomized controlled trials reported conflicting findings. Aims: To investigate the effect of ketamine on emergence agitation in children. Methods: Databases of MEDLINE, EMBASE, and CENTRAL were systematically searched from their start date until February 2019. Randomized controlled trials comparing intravenous ketamine and placebo in children were sought. The primary outcome was the incidence of emergence agitation. Secondary outcomes included postoperative pain score, duration of discharge time, and the adverse effects associated with the use of ketamine, namely postoperative nausea and vomiting, desaturation, and laryngospasm. Results: Thirteen studies (1125 patients) were included in the quantitative meta-analysis. The incidence of emergence agitation was 14.7% in the ketamine group and 33.3% in the placebo group. Children receiving ketamine had a lower incidence of emergence agitation, with an odds ratio being 0.23 (95% confidence interval: 0.11 to 0.46), certainty of evidence: low. In comparison with the placebo, ketamine group achieved a lower postoperative pain score (odds ratio: −2.42, 95% confidence interval: −4.23 to −0.62, certainty of evidence: very low) and lower pediatric anesthesia emergence delirium scale at 5 minutes after operation (odds ratio: −3.99, 95% confidence interval: −5.03 to −2.95; certainty of evidence: moderate). However, no evidence was observed in terms of incidence of postoperative nausea and vomiting, desaturation, and laryngospasm. Conclusion: In this meta-analysis of 13 randomized controlled trials, high degree of heterogeneity and low certainty of evidence limit the recommendations of ketamine for the prevention of emergence agitation in children undergoing surgery or imaging procedures. However, the use of ketamine is well-tolerated without any notable adverse effects across all the included trials. PROSPERO registration: CRD42019131865. © 2019 John Wiley & Sons Ltd